Accreditation as a management tool: a national survey of hospital managers' perceptions and use of a mandatory accreditation program in Denmark - Louise A. Ellis; Anne Nicolaisen; Søren Bie Bogh; Kate Churruca; Jeffrey Braithwaite; Christian von Plessen (BMC, 2020)
Abstract Background This study aimed to examine managers' attitudes towards and use of a mandatory accreditation program in Denmark, the Danish Healthcare Quality Program (Den Danske Kvalitetsmodel [DDKM]) after it was terminated in 2015. Methods We designed a nationwide cross-sectional online survey of all senior and middle managers in the 31 somatic and psychiatric public hospitals in Denmark. We elicited managers' attitudes towards and use of DDKM as a management using 5-point Likert scales. Regression analysis examined differences in responses by age, years in current position, and management level. Results The response rate was 49% with 533 of 1095 managers participating. Overall, managers' perceptions of accreditation were favorable, highlighting key findings about some of the strengths of accreditation. DDKM was found most useful for standardizing processes, improving patient safety, and clarifying responsibility in the organization. Managers were most negative about DDKM's ability to improve their hospitals' financial performance, reshape the work environment, and support the function of clinical teams. Results were generally consistent across age and management level; however, managers with greater years of experience in their position had more favorable attitudes, and there was some variation in attitudes towards and use of DDKM between regions. Conclusion Future attention should be paid to attitudes towards accreditation. Positive attitudes and the effective use of accreditation as a management tool can support the implementation of accreditation, the development of standards, overcoming disagreements and boundaries and improving future quality programs.